2013
DOI: 10.14693/jdi.v19i2.138
|View full text |Cite
|
Sign up to set email alerts
|

Theobromine Effects on Enamel Surface Microhardness: In Vitro

Abstract: Dental caries is still a dental health problem in Indonesia. Fluoride, one of the dental caries prevention materials but its safety and the danger of fluorosis is still debated. Theobromine is an alkaloid compounds contained in cocoa beans. Theobromine is believed to increase enamel microhardness with mineral changes in the enamel superficial layer. Objectives: To determine the influence of Theobromine on the enamel surface microhardness. Effective dose of theobromine to affect enamel hardness will be determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 8 publications
1
9
0
3
Order By: Relevance
“…Some research on Theobromine (3.7-dimethylxantine) contained in the cocoa fruit extracts, found that theobromine can be used as a natural ingredient to prevent dental caries. 8 Sadeghpour's study on animals, reveals that Theobromine was more effective in preventing caries compare to fluorine. Application of theobromine to the enamel surface will increase the size of hydroxyapatite crystals that will improve enamel resistance to acids so as to prevent demineralization.…”
Section: 4mentioning
confidence: 99%
See 2 more Smart Citations
“…Some research on Theobromine (3.7-dimethylxantine) contained in the cocoa fruit extracts, found that theobromine can be used as a natural ingredient to prevent dental caries. 8 Sadeghpour's study on animals, reveals that Theobromine was more effective in preventing caries compare to fluorine. Application of theobromine to the enamel surface will increase the size of hydroxyapatite crystals that will improve enamel resistance to acids so as to prevent demineralization.…”
Section: 4mentioning
confidence: 99%
“…Application of theobromine to the enamel surface will increase the size of hydroxyapatite crystals that will improve enamel resistance to acids so as to prevent demineralization. 5,7,8 The tooth enamel surface hardness can be affected by the exchange of minerals on the surface of the enamel. Kargul 14 found that Theobromine 200 mg/L which is applied to the surface of tooth enamel remineralization effect in the process to increase hardness of tooth enamel.…”
Section: 4mentioning
confidence: 99%
See 1 more Smart Citation
“…Pendahuluan Senyawa-senyawa turunan xantin seperti teobromin diketahui memiliki beberapa aktivitas farmakologi, diantaranya sebagai bronkodilator, antioksidan, anti kanker dan baru-baru ini teobromin tebukti dapat meningkatkan kekerasan mikro email pada gigi dengan terjadinya perubahan mineral pada lapisan permukaan email. 2 Meskipun penggunaannya sebagai obat anti asma telah cukup dikenal, teobromin saat ini mulai dikembangkan juga dalam pemeliharaan kesehatan gigi, tetapi turunan xantin diketahui memiliki efek samping yang kurang menguntungkan yaitu penekanan pada jantung dan sistem saraf pusat. [1][2][3] Beberapa penelitian mengenai modifikasi struktur xantin untuk telah dilakukan sehingga diperoleh turunan senyawa xantin yang lebih poten dan selektif salah satunya dengan mensubsitusi pada atom N 1 xantin.…”
unclassified
“…2 Meskipun penggunaannya sebagai obat anti asma telah cukup dikenal, teobromin saat ini mulai dikembangkan juga dalam pemeliharaan kesehatan gigi, tetapi turunan xantin diketahui memiliki efek samping yang kurang menguntungkan yaitu penekanan pada jantung dan sistem saraf pusat. [1][2][3] Beberapa penelitian mengenai modifikasi struktur xantin untuk telah dilakukan sehingga diperoleh turunan senyawa xantin yang lebih poten dan selektif salah satunya dengan mensubsitusi pada atom N 1 xantin. 1,[4][5] Meskipun teobromin dianggap sebagai zat beracun, ia dilaporkan memiliki beberapa aktifitas farmakologi seperti anti kanker, diuretik, stimulan kardiak, hypocholesterolemic, relaksan otot halus, vasodilator asma dan koroner.…”
unclassified